Wartime and Online Education: A Bibliometric Analysis - Babalola, Sunday Samson; Genga, Cheryl Akinyi (Research in Social Sciences and Technology- OpenED Network, 2025)
This study sheds light on the existing void regarding wartime and online education in Africa. Over three-quarters of African nations have experienced various forms of conflict over the past three decades, resulting in a significant loss of life and immense suffering for African citizens striving for education. The African continent has witnessed nearly 88% of conflict-related fatalities worldwide. The widespread destruction of schools and universities, from primary to higher education, has worsened the problem of limited technology resources. This lack of technology makes it even harder for educational institutions to function effectively. Recent insecurity poses a formidable challenge to many African higher education institutions, impeding efficient administration and management, disrupting academic calendars, claiming student lives, and damaging the critical infrastructure for teaching and learning. In addition, African higher education institutions still lag behind their counterparts on other continents in embracing digital transformation. Using the Scopus database, this study conducted a bibliometric analysis of publications from 2000 to 2024, focusing on wartime and online education. The gathered documents were meticulously analysed using visualisation tools like VOS Viewer. The findings highlight a significant research gap regarding the intersection of wartime conditions and online education in African institutions, as there are no publications on wartime and online learning from the African continent. The findings highlight that the publications are mainly from a Western perspective, which has marginalised African higher education institutions in the global knowledge production and dissemination landscape. The paper identifies promising areas for further research on improving education during African conflicts to guide future efforts.